Improving Puskesmas Services Through Integrated Management Innovation System in Ngawi and Sumenep Regency - Rosidah Rosidah (International Journal of Regional Innovation, 2021)
This study discusses the innovations made in order to overcome problems that arise in innovating in public services such as Puskesmas. This study aims to determine the extent to which innovations carried out by the government with the support of the community can be successful and how their impact on the region, especially Ngawi Regency and Sumenep Regency in improving public services for the local community. This study used qualitative research methods. Data collection is carried out through searching various sources which are then processed and described in the form of narratives according to data needs. The population in this study is an area that has made innovations in order to improve public services, especially Puskesmas. While the research subject is in Ngawi Regency named ADA PUMA (Submit Deed From Public Health Center, District, or RuMah) Kabupaten Ngawi and Kabupaten Sumenep named the innovation “Si Mantap Puas” (Integrated Management System for Community Satisfaction) Guluk Guluk Health Center. This study shows that the innovations carried out by the government supported by the local community have succeeded in creating an innovative system in order to improve public services at the Puskesmas. The two innovations created by Ngawi Regency and Sumenep Regency have succeeded in facilitating public services at the Puskesmas in their respective regions, which of course is directly proportional to community satisfaction with the services provided. This study shows that the innovations carried out by the government supported by the local community have succeeded in creating an innovative system in order to improve public services at the Puskesmas. The two innovations created by Ngawi Regency and Sumenep Regency have succeeded in facilitating public services at the Puskesmas in their respective regions, which of course is directly proportional to community satisfaction with the services provided. This study shows that the innovations carried out by the government supported by the local community have succeeded in creating an innovative system in order to improve public services at the Puskesmas. The two innovations created by Ngawi Regency and Sumenep Regency have succeeded in facilitating public services at the Puskesmas in their respective regions, which of course is directly proportional to community satisfaction with the services provided.